Formononetin and Dihydroartemisinin Act Synergistically to Induce Apoptosis in Human Acute Myeloid Leukemia Cell Lines - Yusef Abbasi; Marziyeh Pooladi; Roya Nazmabadi; Jamal Amri; Helia Abbasi; Hadi Karami (Cell Journal, 2024)
Objective: Enhanced cell survival and drug resistance in tumor cells have been linked to the overexpression of antiapoptoticmembers of the Bcl-2 family proteins, including Bcl-2 and Mcl-1. The aim of this study was to explore theimpact of formononetin and dihydroartemisinin combination on the growth and apoptosis of acute myeloid leukemia(AML) cells.Materials and Methods: In this experimental study, the cell survival and cell proliferation were tested by MTT assay andtrypan blue staining. The evaluation of cell apoptosis was conducted using Hoechst 33342 staining and a colorimetricassay to measure caspase-3 activity. To determine the mRNA levels of Mcl-1, Bcl-2, Bax, and Cyclin D1, a quantitativereal-time polymerase chain reaction (qRT-PCR) was performed.Results: We showed that treatment with either formononetin or dihydroartemisinin alone, led to significant decreasein the cell survival and growth, and triggered apoptosis in U937 and KG-1 AML cell lines. Moreover, treatment witheach of the compounds alone significantly decreased the mRNA levels of Mcl-1, Bcl-2 and Cyclin D1 mRNA, while, theexpression level of Bax mRNA was enhanced. Combination of two compounds showed a synergistic anti-cancer effect.Conclusion: The anti-leukemic potential of formononetin and dihydroartemisinin is exerted through the effect on cellcycle progression and intrinsic pathway of apoptosis. Therefore, they can be considered as a potential anti-leukemicagent alone or along with existing chemotherapeutic drugs.